Sequential hybridization may have facilitated ecological transitions in the Southwestern pinyon pine syngameon. Issue 6 (19th November 2022) - Buck, Ryan; Ortega‐Del Vecchyo, Diego; Gehring, Catherine; Michelson, Rhett; Flores‐Rentería, Dulce; Klein, Barbara; Whipple, Amy V.; Flores‐Rentería, Lluvia
Summary: Multispecies interbreeding networks, or syngameons, have been increasingly reported in natural systems. However, the formation, structure, and maintenance of syngameons have received little attention. Through gene flow, syngameons can increase genetic diversity, facilitate the colonization of new environments, and contribute to hybrid speciation. In this study, we evaluated the history, patterns, and consequences of hybridization in a pinyon pine syngameon using morphological and genomic data to assess genetic structure, demographic history, and geographic and climatic data to determine niche differentiation. We demonstrated that Pinus edulis, a dominant species in the Southwestern US and a barometer of climate change, is a core participant in the syngameon, involved in the formation of two drought‐adapted hybrid lineages including the parapatric and taxonomically controversial fallax ‐type. We found that species remain morphologically and genetically distinct at range cores, maintaining species boundaries while undergoing extensive gene flow in areas of sympatry at range peripheries. Our study shows that sequential hybridization may have caused relatively rapid speciation and facilitated the colonization of different niches, resulting in the rapid formation of two new lineages. Participation in the syngameon may allow adaptive traits to be introgressed across species barriers and provide the changes needed to survive future climate scenarios. Abstract : See also the Commentary on this article by Whittemore & Miller, 237 : 1943–1945.